Endowed Value or Imposed Heritage? Attitudes of Russian-Speaking Lithuanian Citizens towards their Native Language - Lichačiova, Ala; Markova, Svetlana (Taikomoji kalbotyra, 2014)
So far there has been no detailed research done in Lithuania that would allow to analyze the attitudes of the Russian-speaking citizens towards their native language. In this article, an attempt is made to determine the subtle relation between the Lithuanian citizens of non-Lithuanian nationality and the Russian language which is considered to be native in their families, while they either are Russians or identify themselves as Russians.Certain questions concerning this problem are taken into consideration: do Russian-speaking citizens feel good about using their native language; do they feel affinity to Russia as their symbolic homeland or the mother country of their language; do they want their children to have a good command of Russian and consider it their native language; is their relationship with their native language affected by the manifestation of Russophobia in public discourse and mass media.The data of the sociolinguistic projects Language Use and Ethnic Identity in Lithuanian Cities (2007–2009) and A Sociolinguistic Map of Lithuania (2010–2012) focussing on Vilnius, Klaipėda and Visaginas is discussed. These cities have been selected as the ones with the largest Russian-speaking population as compared to other regions of Lithuania.The analysis of in-depth interviews reveals that for the Russian-speaking people in Lithuania the native language remains the only real indicator of their ethnic self-identification. Most of the respondents do not regard Russia as a country close to them in terms of lifestyle and mentality, they do not perceive Russia as a symbolic concept defining their self-identity; it is for them the space of their mother tongue. The respondents claim that they value their mother tongue, see it as emotionally closest and stress the relation between the Russian language and culture as well as the pragmatic value of knowing Russian nowadays. Young respondents declare that they intend to do their best to pass their mother tongue to their future children.However, the intentions of the Russian-speaking people of Lithuania to support the vitality of their native language, which requires more effort than is usual for people living in the environment of a different language. In the Lithuanian media and online comment sections, ethnic and linguistic intolerance towards local people who speak another language is livened up periodically. Therefore Russian-speaking residents of Lithuania need to be psychologically strong in order to resist the pressure of public discourse and to sustain their native language.
Keywords: native language; Russian language; language attitudes; self-perception; public discourse